Entrapment of gold catalyst in silicon/silicon-oxide nanowires - Li, Feng Ji (2015)
Metal catalyst sometimes is entrapped in crystalline silicon (Si)/amorphous Si-oxide nanowires. Till now, however, the entrapping mechanism is still unclear. In this work, Si/Si-oxide nanowires were grown via thermal annealing of a Si wafer coated with a 10 nm thick layer of gold (Au) which acts as catalyst. Au nanospheres or elongated core are occasionally entrapped in the nanowires. Transmission electron microscopy, energy dispersive X-ray spectroscopy and selected area electron diffraction were employed to study the structure of the grown nanowires and their relationship with the seeding Au particles. The entrapment of the Au catalyst is attributed to the eutectic precipitation of Au and Si in the Si-supersaturated Au–Si–O droplet as the temperature is below the eutectic point. A new mechanism elucidates the entrapping process.